2008
DOI: 10.1111/j.1746-1561.2008.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tobacco Use Among Students Aged 13‐15 Years in Health Ministers’ Council/Gulf Cooperation Council Member States, 2001‐2004

Abstract: For boys and girls, high prevalence of cigarette smoking, high prevalence of shisha use, and high susceptibility of never smokers to initiate smoking in the next year are troubling indicators for the future of chronic disease and tobacco-related mortality in the Member States of the HMC/GCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 3 publications
3
56
1
1
Order By: Relevance
“…This study has found that the prevalence of smokeless tobacco is in fact higher than cigarette smoking, which is consistent with the results from other studies [9,12,17,18,20,21]. Moreover, the prevalence of smokeless tobacco has been reported to be high specifically among young females in this region; for example, in Lebanon,29.9% of young females used smokeless tobacco.…”
Section: Who Fctc Article 21: Reporting and Exchange Of Informationsupporting
confidence: 94%
See 1 more Smart Citation
“…This study has found that the prevalence of smokeless tobacco is in fact higher than cigarette smoking, which is consistent with the results from other studies [9,12,17,18,20,21]. Moreover, the prevalence of smokeless tobacco has been reported to be high specifically among young females in this region; for example, in Lebanon,29.9% of young females used smokeless tobacco.…”
Section: Who Fctc Article 21: Reporting and Exchange Of Informationsupporting
confidence: 94%
“…During the last decades, there have been several attempts to understand and measure the rise in tobacco use among the youth in this part of the world using different methodologies [12,13,[16][17][18][19][20][21][22][23]; however, no papers describing and linking changes in tobacco use over time in this region have been published as far as the researchers of this study are aware of.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of ever cigarette smoking among high school students ranged from 14.4% in Oman to 23.9% in Bahrain (Al-Mulla et al, 2008), (21.7%) in secondary school students of Saudi Arabia (Amin et al, 2011) and 29.6% in High-School students from Greece (Lazaros et al, 2009). A study of 635 students in rural secondary schools in the Nile Delta region found that 11.5% of male students reported current smoking (Harbour, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed that although 63.9% of the smokers expressed the desire to quit smoking about 27.6% were unable to quit in a period of one year (WHO, CDC, 2010). Results published for GYTS for students of the same age group and same period in other Gulf Cooperation Council (GCC) members countries, were similar, however, shisha was more used than cigarette (Al-Mulla et al, 2008). A more recent survey of GYTS conducted in neighboring Iraq in 2012 for same age group yielded slightly lower results.…”
mentioning
confidence: 80%